Novos rumos, velhos hábitos: debates acerca do trabalhador rural na Assembléia Nacional Constituinte Portuguesa de 1911 - Russo, Renan Henrique Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Portugal, in 1911, was in the midst of a turbulent political change. The newly installed Republican government was intended to be democratic, supporter of universal suffrage and solver of the labor crisis in the country. However, some practices were not consistent with the theory. The reflections came in the National Constituent Assembly of 1911. We believe that by analyzing the institution that legislated on the directions of Republic, it should be founded discussions that included the country‟s majoriarian professional class: rural workers. We stress that expect a stronger stance, on the part of politicians, to the causes of that class is not anachronism. Authors like Leon Poinsard, Basílio Teles, José Picão and other contemporaries, already indicated the best use of these classes as the key to the national economy, since they were the main source of export country, as well as basis for other industries. It is on this issue that focuses this work.

Portugal, em 1911, encontrava-se em meio a uma turbulenta mudança política. O recém-instalado governo republicano se pretendeu democrático, defensor do sufrágio universal e solucionador da crise do trabalho no país. Porém, algumas práticas não foram condizentes com a teoria. O reflexo disso veio na Assembleia Nacional Constituinte de 1911. Acreditamos que, ao analisar a instituição que legislava sobre os rumos da República, se deveriam encontrar debates que incluíssem a camada profissional majoritária do país: os trabalhadores rurais. Sublinhamos que esperar uma postura mais incisiva, por parte dos políticos, para com as causas do campo não é anacronismo. Autores como Leon Poinsard, Basílio Teles, José Picão e outros contemporâneos já apontavam o melhor aproveitamento destas classes como chave para a economia nacional, já que eram a principal fonte de exportação do país, além de base para outras indústrias. É sobre esta questão que se debruça o presente trabalho
Keywords: Politica de mão-de-obra agricola; Economia agrícola - Portugal; Trabalhadores rurais; Portugal - Historia - Revolução - 1910; Agriculture - Economic aspects